A Practical Approach to Gear Design and Lubrication: A Review - Dario Croccolo; Massimiliano De Agostinis; Giorgio Olmi; Nicolò Vincenzi (Lubricants, 2020)
The modern design of mechanical parts, such as gears, goes through the continuous demand for a high level of efficiency and reliability, as well as an increased load carrying capacity and endurance life. The aim of the present paper was to perform a review and to collect practical examples in order to provide interesting tips and guidelines for gear design, including both its dimensioning and its lubrication. From this point of view, this paper is particularly novel, as it is a full-comprehensive collection of all the tools supporting gear design. Several practical aspects have been taken into account, including the definition of the right profile shifting, the selection of a proper lubricant, and the definition of the quality grade and of the tolerances needed to obtain the correct backlash. Finally, a numerical example is provided, addressing the research of the best solution to fit a given space, while maximizing the transmittable torque over weight ratio for two mating spur gears.